PENDAMPINGAN BALITA GIZI KURANG DENGAN PEMBERIAN MAKANAN TAMBAHANBERBAHAN DASAR BISKUIT PMT - Tutut Pujianto; Frenky Arif Budiman; Wahyu Wibisono (Prosiding Conference on Research and Community Services, 2019)
Malnourished toddler can be caused by inappropriate supplementary feeding, ignorance of the good way of feeding, and habits that are harmful to health. Malnourished toddlers will grow small, thin, and short which have an impact to their cognitive abilities, low intelligence, and the decrease of productivity. In order to overcome the malnourished on the group of toddler, Supplementary Food Feeding (PMT) is a way to solve the problem. The PMT biscuit programs tends to be unsuccessful because the toddler boredom to the biscuit approximately in a week. Therefore it is necessary to modify the biscuits into toddlers’ favorite food, so that it can improve the nutritional status of the toddlers. The assistance of malnourished toddler was done to 8 toddlers of Desa Pelem Kecamatan Pare Kabupaten Kediri. The determination of malnourished toddler status was done by doing 24-hour recall. From the recall results, it also obtained data of energy consumption level of toddlers. The making of supplementary food by PMT biscuit as the basis material was done by paying attention to the energy, protein, fat and carbohydrate content, which was given in 14 days. The evaluation of the assistance was done by comparing the weight of a toddler before and after the giving of PMT as well as changes in the level of energy consumption, protein, fat and carbohydrates. The results showed that 62.5% experienced an increase in body weight, 25% did not experience a change in body weight, and 12.5% experienced a decrease in body weight. Toddlers who experienced weight loss was occurred because at the time of the assistance, they suffered from dengue hemorrhagic fever (DHF). While toddlers who did not experience changes in body weight was occurred because of coughs and colds. The increase of weight that occurred in 62.5% of children under five was in the range of 0.1 kg to 0.5 kg, while the level of the consumption of energy, protein, fat and carbohydrates has also increased. Based on the results of the assistance, PMT is necessary to be continued. In order to be more successful in the assistance program, parents of the toddler need to be given additional knowledge of the menu variations